2012
DOI: 10.1088/1475-7516/2012/02/001
|View full text |Cite
|
Sign up to set email alerts
|

CLUES on Fermi-LAT prospects for the extragalactic detection of μνSSM gravitino dark matter

Abstract: The µνSSM is a supersymmetric model that has been proposed to solve the problems generated by other supersymmetric extensions of the standard model of particle physics. Given that R-parity is broken in the µνSSM, the gravitino is a natural candidate for decaying dark matter since its lifetime becomes much longer than the age of the Universe. In this model, gravitino dark matter could be detectable through the emission of a monochromatic gamma ray in a two-body decay. We study the prospects of the Fermi-LAT tel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 59 publications
0
45
0
Order By: Relevance
“…The available data cover a photon energy range from 10's of GeV down to a few keV, providing the possibility of exploring a much broader range of DM candidates than WIMPs. Indeed, some of these data have already been utilized to constrain LDM, see, e.g., [33][34][35][36][37][38][39][40][41][42][43][44]. Sterile neutrinos with a mass ∼ O(1 − 10 keV) are a particularly popular candidate and their constraints have been explored in, e.g., [36, 38-40, 45-51, 51-57].…”
Section: Jhep11(2013)193mentioning
confidence: 99%
“…The available data cover a photon energy range from 10's of GeV down to a few keV, providing the possibility of exploring a much broader range of DM candidates than WIMPs. Indeed, some of these data have already been utilized to constrain LDM, see, e.g., [33][34][35][36][37][38][39][40][41][42][43][44]. Sterile neutrinos with a mass ∼ O(1 − 10 keV) are a particularly popular candidate and their constraints have been explored in, e.g., [36, 38-40, 45-51, 51-57].…”
Section: Jhep11(2013)193mentioning
confidence: 99%
“…Other analyses concerning cosmology such as gravitino dark matter and electroweak baryogenesis can be found in Refs. [37,38] and in Ref. [39], respectively.…”
Section: Constraints From Atlasmentioning
confidence: 94%
“…If the RPV parameter |Uγ ν | from the 7 × 7 neutralino mixing matrix is between 10 −16 and 10 −12 , the correct neutrino masses are reproduced. Values of the gravitino mass larger than 10 GeV are disfavoured, as well as lifetimes smaller than about 3 to 5 × 10 27 s. Further studies on the prospects of the Fermi-LAT telescope to detect such monochromatic lines in five years of observations of the most massive nearby extragalactic objects have been performed [38]. It was found that a gravitino with a mass range of 0.6 − 2 GeV, and with a lifetime range of about 3 × 10 27 − 2 × 10 28 s would be detectable by the Fermi-LAT with a signal-to-noise ratio larger than 3. it has also been shown that gravitino masses larger than about 4 GeV are already excluded in the μνSSM by Fermi-LAT data of the galactic halo [37].…”
Section: Signatures At Lhc: Displaced Verticesmentioning
confidence: 99%
“…The detection of gravitino DM in several RPV scenarios has been studied in the literature considering the case of gravitinos emitting gamma rays when decaying in the smooth galactic halo and extragalactic regions at cosmological distances [18,21,19,22,23], and also in nearby extragalactic structures [24]. In the interesting case of the galactic halo, the gamma-ray signal is an anisotropic sharp line and the flux is given by…”
Section: Detection Of Gravitino Dark Mattermentioning
confidence: 99%